Knowledge and attitudes towards brain death and organ donation in hospitalized patients and their relatives - Yilmaz, Yeliz; Acar, Kadriye; Oyur Celik, Gulay; Kamer, Erdinc; Er, Ahmet (Annals of Medical Research, 2021)
Aim: Organs are generally procured from cadavers in developed countries while they are mostly obtained from living donors in developing countries. Firstly, the diagnosis of brain death should be established in order to obtain organ from a cadaver. Secondly, the family or legal guardian should have to donate organs. The knowledge and attitudes of relatives of donor towards organ donation is important in a patient diagnosed as brain death. Thus, this study was performed to determine knowledge and attitudes towards brain death and organ donation in patients (their relatives) hospitalized in general surgery clinic where organ donation is performed. Material and Methods: The patients hospitalized in General Surgery Clinic, and their relatives (n=80) were included to the study. The clinic also performed renal transplantation. The questionnaires developed by researchers were used to collect data.Results: Of the subjects included, 75% were women while25% were men. Mean age was 40.71±15.53 years. Majority of subjects had inadequate knowledge about brain death or organ transplantation. Of subjects, 76.25% reported that they support organ donation. Only 2.5% had donated their organs. Subjects(n=19) reporting that they would not donate organ of their relative diagnosed as brain death proposed following reasons: religious thoughts(15.8%), refusal of disrupting body integrity(94.8%) and being blinded to decision of potential donor about organ donation.Conclusion: Although sample size is small in our study, it was shown that majority of individual have no sufficient information about brain death and organ transplantation and that organ donation rates are extremely in our society.
Keywords: Attitude; brain death; knowledge; organ transplantation; practice